Problem-Based Learning Model to Improve English Learning Achievement - Hamzah Alias (ETDC: Indonesian Journal of Research and Educational Review, 2023)
Examining the language components, textual organization, and social function of statements that provide services and answers based on usage context is one of the most challenging assignments for students. It is necessary to find a remedy because student achievement data from recent years indicates that they are quite poor when it comes to studying this content. Thus, 32 students from class XI MA As'diyah Putri Sengkang served as subjects for a classroom action study that was conducted. English learning achievement is the subject of the study. Determining and assessing the PBL model's efficacy in raising English learning outcomes is the goal of this study. Utilizing learning accomplishment exams, data was gathered and subjected to both qualitative and descriptive analysis. If this action research attains a minimum average score of 75 and a minimum of 82% for classical learning completeness, it is considered effective. According to the study findings, cycle I had an average score of 72.21 and 75.64% for classical completeness. In cycle II, on the other hand, classical completeness reached 92.48%, and the average score was 74.32. In the second semester of the 2022-2023 academic year, the class XI MA As'adiyah Putri Sengkang students can attain better learning outcomes by implementing the PBL learning model in two cycles.